2019
DOI: 10.1021/jacs.9b11197
|View full text |Cite
|
Sign up to set email alerts
|

Evolution Pathway from Iron Compounds to Fe1(II)–N4 Sites through Gas-Phase Iron during Pyrolysis

Abstract: Pyrolysis is indispensable for synthesizing highly active Fe-N-C catalysts for the oxygen reduction reaction (ORR) in acid, but how Fe, N, and C precursors transform to ORR-active sites during pyrolysis remains unclear. This knowledge gap obscures the connections between the input precursors and output products, clouding the pathway toward Fe-N-C catalyst improvement. Herein, we unravel the evolution pathway of precursors to ORR-active catalyst comprised exclusively of single atom Fe1(II)-N4 sites via in-tempe… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

11
176
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 226 publications
(188 citation statements)
references
References 38 publications
11
176
1
Order By: Relevance
“…[46][47][48] An important step toward a better understanding of this promising substitution material for platinum electrodes is to clarify the structure and electronic properties of the active site. [39,43,49,50] The current consensus in the literature is that the catalytically active iron ion is surrounded by 2-4 nitrogen donor atoms embedded in a graphene sheet that may have structural or electronic defects and possibly an additional axial ligand. [39,49,51,52] The sketch shown in Figure 1A attempts to summarize the types of environment discussed in the literature.…”
Section: Introductionmentioning
confidence: 99%
“…[46][47][48] An important step toward a better understanding of this promising substitution material for platinum electrodes is to clarify the structure and electronic properties of the active site. [39,43,49,50] The current consensus in the literature is that the catalytically active iron ion is surrounded by 2-4 nitrogen donor atoms embedded in a graphene sheet that may have structural or electronic defects and possibly an additional axial ligand. [39,49,51,52] The sketch shown in Figure 1A attempts to summarize the types of environment discussed in the literature.…”
Section: Introductionmentioning
confidence: 99%
“…Kumar et al reported that iron-containing particles also show moderate initial ORR activity in acidic electrolyte besides the atomic distributed Fe-N-C catalyst [ 12 ]. Other groups showed much lower activities for iron particles in acidic media compared to atomic Fe-N x sites [ 13 , 14 ]. This is the reason why unprotected iron-containing particles are commonly removed by an additional step of acid leaching after pyrolysis [ 5 ].…”
Section: Introductionmentioning
confidence: 99%
“…The metallic Fe (PDF #06-0696) as the predominant phase in F-NCS is also confirmed by XRD ( Figure 3h). The use of 5 vol% H 2 facilitates to form metallic Fe at 200 °C rather than iron oxides, [34,35] Figure 1. Interactive facilitation and stabilization between Rh and Fe.…”
mentioning
confidence: 99%